The Relationship Between the Biokinetic Parameters of an Aerobic Granular Sludge System and the Applied Operating Conditions - Hamiruddin, Nur Ain; Awang, Nik Azimatolakma (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Biokinetic parameters help to describe the rate of substrate utilization and biomass production or growth by microbial action, which is important to the design process and performance optimization of wastewater treatment. Although studies of the biokinetic parameters of aerobic granular sludge (AGS) systems have been increasing lately, the significance for each value in terms of maximum specific growth rate, substrate concentration at one-half of the maximum specific growth rate (KS), and cell yield (Y) in relation to the applied operating conditions are rarely discussed.
Keywords: granular sludge system; biokinetic parameters; organic loading rate; OLR; sewage; operating conditions; szlam ziarnisty; parametry biokinetyczne; wskaźniki organiczne; ścieki; warunki eksploatacji